Delivering the ornament (Raton Range Raton, NM, 1990)
This article is about Ema Foree receiving an ornament for her donation to the Lions Club for the City of Bethlehem.
Newspaper Article + photograph of Delmar Sims and Emma Foree
Master list item #: 14
File location is in the Raton file Cabinet
Keywords: Sims, Delmar -- Raton Lions Club Member; Foree, Emma -- Contributor; Raton Lions Club; Christmas Ornaments; Christmas Donations; Donor Rewards; City of Bethlehem; Raton, New Mexico